SURGICAL APPROACH IN THE ORO-MAXILO-FACIAL SPHERE OF THE PATIENT WITH NEURO-PSYCHOLOGICAL PATHOLOGY EPILEPSY - Ana Maria Zaharescu; Carolina Susanu; Șerban Paul Popa; Oana Lorena Nistor; Mădălina Nicoleta Matei; Daniela Laura Buruiană; Cristian Constantin Budacu (Romanian Society of Oral Rehabilitation, 2021)
Praxis in dentistry does not start with fear of accidents et complications, less emergencies, but in order to help prevent and treat effectively, they have been known and readily diagnosed correctly and with responsibility. Fortunately, in the dental practice, emergency is not frequently met, but if it occurs nonetheless, the properly and fast reaction of the doctor can save the patient's life.Emergency asks for a maximum efficiency, and its addressing requires the most direct and shorter resolution. Epilepsy is neurological functional pathology that changes the way of transmitting electrical signals in the brain.Material and methods: The study was carried out in the Clinic of Oral and Maxillofacial Surgery,on 121 patients, studied in the period 2017 -2020 . Out of them, 104 have been emergencies.Results and Discussions: As regarding the interventions suffered by the patients it was noticed that the most frequently neurological emergency installed within dentistry and oral-maxillofacial is seizures. Conclusions: Epileptic crises (of varying intensity) may occur of different causes and in defferent the intervals, a responsible anamnesis informs the doctor about the frequency and severity of crisis.